Migrant Intimacies in the “Land of Opportunity”: Navigating Race, Class, and Status in Hong Kong’s Entertainment District - Wo, Lai (Anthropologica)

(untitled) (University of Victoria, 2023)
Since the 1970s, Southeast Asia women have turned to outward labour migration to Hong Kong to enhance their economic livelihoods. However, while their overseas work afforded the possibility of improved material conditions back home, migrants face an array of ethnic, classed, and gendered subjugations during their temporary placements abroad. Hopeful for futures beyond domestic labour, some migrant workers engage in intimate exchanges with Euro-American expatriate men in Hong Kong’s entertainment district in Wanchai. Indeed, these relations do not entirely offset their ethnic and classed minoritization. But, becoming short-term partners, long-term girlfriends, or eventual wives provide alternative pathways for navigating their disenfranchisement as racialized labourers relegated to the city’s spatial and legal peripheries. Comparably, their expatriate male partners also conveyed their own subjective experiences of dislocation and suffering due to employment redundancy, aging, and past separations. Ethnographic research examining the intimacies forged between these two groups of foreigners in Hong Kong—Southeast Asian migrants seeking better futures, and Euro-American men healing from past employment and emotional traumas—reveal opportunities for expanded aspirational capacities, broadened orientations to the future, and alternative gendered subjectivities. This article explores how the intimacies fostered in Wanchai carve out opportunity to re-envision what might be affectively and materially possible in their futures beyond domestic labour, aging alone, and prolonged economic precarity.